Teknik Pengambilan Gambar dalam Program Siaran Berita tvMu - Miftahul Kabila; Hiru Muhammad (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
In the tvMu news broadcast program, a shooting technique that can produce good video quality is needed to be broadcast. Because this shooting technique is needed in visual communication technology, especially in the field of videography. The purpose of this study is to determine the shooting angle in the tvMu news broadcast program and to determine the image size that determines the quality of the content of the tvMu news broadcast program that is broadcast. This study uses a qualitative method that is used to explain how the shooting technique is in the tvMu news broadcast program. This tvMu news broadcast is presented to obtain information about the association and national that can invite important figures of Muhammadiyah. This was done through in-depth interviews with several informants and triangulation. The results of this study revealed the shooting techniques used in tvMu news broadcasts, including various shooting types, image composition, aspect ratio, frame size, and camera movements.customers.